Distortion and Subversion Punk Rock Music and the Protests for Free Public Transportation in Brazil (1996-2011) - Lopes de Barros, Rodrigo (Liverpool University Press, 2022)
At the turn of the twenty-first century, the Brazilian punk and hardcore music scene joined forces with political militants to foster a new social movement that demanded the universal right to free public transportation. These groups collaborated in numerous venues and media: music shows, protests, festivals, conferences, radio stations, posters, albums, slogans, and digital and printed publications. Throughout this time, the single demand for free public transportation reconceptualized notions of urban space in Brazil and led masses of people across the country to protest. This book shows how the anti-capitalist, anti-bourgeoisie stance present in the discourse of a number of Brazilian bands that performed from the late 1990s to the beginning of the twenty-first century in the underground music scenes of Florianópolis and São Paulo encountered a reverberation in the rhetoric emanating from the Campaign for the Free Fare, subsequently known as the Free Fare Movement (Movimento Passe Livre, or MPL). This allowed the engaged bands and the movement for free public transportation to contribute to each other's development. The book also includes reflections on the Bus Revolt that occurred in the northeastern city of Salvador, unveiling traces of the punk and anarcho-punk movements, and the Revolution Carnivals that occurred in the city of Belo Horizonte, an event that mixed lectures, vegetarianism, protests, soccer, and punk rock music.